Polypeptide Fraction from Arca subcrenata Induces Apoptosis and G2/M Phase Arrest in HeLa Cells via ROS-Mediated MAPKs Pathways - Hu, Xianjing (Evid Based Complement Alternat Med, 2015)
Arca subcrenata is documented in the literature of marine Traditional Chinese Medicine. Polypeptide fraction from A. subcrenata, coded as P2, was demonstrated to possess significant antitumor activity in our previous study. However, the underlying mechanism remains undefined. The present study was carried out to investigate the underlying antitumor mechanism of P2 in human cervical cancer HeLa cells by MTT, FCM, LSCM, and western blot assays. The results revealed that P2 significantly induced apoptosis of HeLa cells in a concentration- and time-dependent manner. High level of ROS was provoked by P2, which was in turn responsible for induction of apoptosis through activation of intrinsic mitochondrial pathway and JNK1/2, p38 MAPK pathways, as well as inhibition of ERK1/2 pathway, as evidenced by the abrogation of P2's effect on HeLa cells preincubated with the ROS scavenger NAC. P2 also was observed to display significant effect on G2/M phase arrest by downregulating the expression of cyclin B1/cdc2 complex and upregulating the expression of p21. These findings demonstrate that P2 induces apoptosis and G2/M phase arrest in HeLa cells through ROS-mediated MAPKs pathways, suggesting that P2 would be worth investigating as a promising agent within the scope of marine drugs for treatment of cervical cancer.